Hidden prevalence of chronic kidney disease in hypertensive patients: the strategic role of primary health care. (November 2016) - da Silva, L.S.; Cotta, R.M.M.; Moreira, T.R.; da Silva, R.G.; Rosa, C. de O.B.; Machado, J.C.; da Silva, L.S.; Bastos, M.A.P.
Abstract: Objective: To identify the hidden prevalence of chronic kidney disease (CKD) in hypertensive patients. Study design: Cross-sectional study of individuals with systemic arterial hypertension (SAH) who were registered for primary health care (PHC). Methods: In total, 293 individuals participated. Data were collected through interviews, as well as biochemical and anthropometric assessments. The CKD-EPI formula was used to identify the occurrence of CKD. Pearson's chi-squared test or Fisher's exact test were used to compare proportions. Prevalence ratios were estimated with a confidence interval of 95% for associations between the explanatory variables and CKD. Results: Most of the individuals assessed were female (74%), elderly (69%), with a low income (90%), low education levels (84%) and overweight (66.9%). A CKD prevalence of 38.6% (95% CI: 33.0–44.2) was found and approximately 14% were at an advanced stage of the disease. Upon comparison of the variables in the different stages of CKD, statistically significant association could be suggested between CKD and age, education, alcohol intake, overweight individuals, cardiovascular risk, abnormal creatinine and abnormal microalbuminuria. When the prevalence ratio was assessed, association could be suggested between CKD and age, and CKD and creatinine. Conclusion: The high hidden prevalence of CKD confirms the need to train health professionals involved in the treatment of SAH through PHC, enabling the prevention and diagnosis of CKD in its early stages.